1993
DOI: 10.3758/bf03206944
|View full text |Cite
|
Sign up to set email alerts
|

Covert effects of alcohol revealed by event-related potentials

Abstract: Contradictory evidence as to the effects of alcohol on early information processing stages has been obtained from behavioral and psychophysiological investigations. In the present study, choice reaction times, error rates, and event-related potentials (ERPs) were recorded in a task in which variations in stimulus discriminability and of the (task irrelevant) correspondence between stimulus location and response location were orthogonally combined. Both discriminability and stimulus-response correspondence affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…Second, in incompatible trials of the Simon task, the stimulus activates the spatially corresponding (hence, incorrect) response to a considerable degree, which is reflected in the lateralized readiness potential (LRP; De Jong et al, 1994;Sommer, Leuthold, & Hermanutz, 1993), a measure of hand-specific response activation, and sub-threshold motor activity in the wrong hand (Zachay, 1991). The finding that this activation is temporally stimulus-locked, not response-locked, implies that the point in time when irrelevant spatial information is transmitted to response stages does not depend on the duration of stimulus-identification processes and, thus, not on the point in time when the relevant information is transmitted.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in incompatible trials of the Simon task, the stimulus activates the spatially corresponding (hence, incorrect) response to a considerable degree, which is reflected in the lateralized readiness potential (LRP; De Jong et al, 1994;Sommer, Leuthold, & Hermanutz, 1993), a measure of hand-specific response activation, and sub-threshold motor activity in the wrong hand (Zachay, 1991). The finding that this activation is temporally stimulus-locked, not response-locked, implies that the point in time when irrelevant spatial information is transmitted to response stages does not depend on the duration of stimulus-identification processes and, thus, not on the point in time when the relevant information is transmitted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the target P3 amplitude could be modulated by the arousal states of subjects due to natural or environmental factors (for a detailed review, see Polich and Kok, 1995). More difficult tasks produce larger P3 amplitudes due to the increased arousal states of the subjects (Sommer et al, 1993) and so does the presentation of motivating instructions (Carrillo-de-la-Pena and Cadaveira, 2000). In the current study, the overall larger P3 component for German musicians in the deviant condition is mainly originating from session 1 (first exposure to stimuli).…”
Section: 2mentioning
confidence: 99%
“…When, in a given trial, the spatial stimulus and response codes correspond, this facilitates S-R translation and speeds up the response, whereas noncorresponding codes lead to a response conflict because the incorrect response code is erroneously activated. In fact, electrophysiological studies have shown that presenting a stimulus in a Simon-type task more or less automatically induces response-related activation in the spatially corresponding hand, such as lateralized readiness potentials (De Jong, Liang, & Lauber, 1994;Eimer, 1995;Sommer, Leuthold, & Hermanutz, 1993) or subthreshold electromyographical potentials (Zachay, 1991). This suggests that the codes of spatial stimuli and responses overlap, which again implies that perception and action operate on the same spatial maps (Rizzolatti, Riggio, & Sheliga, 1994).…”
Section: Stimulus-response Compatibilitymentioning
confidence: 99%